BEYOND THE CODE SWITCHING IN WHATSAPP CHATS OF JAVANESE ENGLISH TEACHERS FORUM IN TULUNGAGUNG - Zamili, Qoni' (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2018)
Abstract:(Title: Beyond the Code Switching in Whatsapp Chats of Javanese English Teachers Forum in Tulungagung). Code-switching, the alternate use of more than one language in a discourse, is one of the language phenomena that commonly happens in a communication among bilingual or multilingual people. Recently, the rapid development of technology gives significance effect to the way people communicate such as the blurring of the spoken and written distinction happened in whatsapp chats. Although whatsapp chats uses the written medium, the language used is less correct and less coherent than standard written language, making it closer to speech. It also arise code-switching phenomena among English teachers chat. This study aims to seek the teachers' motives of producing code-switching in their utterances. 30 whatsapp chat screenshots were collected to be analyzed. Furthermore, interviews were conducted to obtain more comprehensive motives from the the Javanese English Teacher Forum members. The results show that most of teachers intentionally and consciously made code-switching for the sake of poetic (joke) and phatic functions. None of them employ code-switching for directive function. In addition, from the perspective of psycholinguistics, this phenomenon could be the result of the LTM (Long Term Memory) subconscious effect of the speakers' cultural background. Keywords: Code switching, Whatsapps chats, Javanese English teacher, poetic function